Prevalence of Gastric Subepithelial Tumors in Korea: A Single Center Experience - Lee, Jung Hoon; Lee, Hang Lak; Ahn, Yong Woo; Lee, Kang Nyeong; Jun, Dae Won; Lee, Oh Young; Han, Dong Soo; Yoon, Byung Chul; Choi, Ho Soon (The Korean journal of gastroenterology, 2015)
The incidental finding of gastrointestinal subepithelial tumors (SETs) is increasing with national cancer screening endoscopy. In a Swedish population, screening endoscopy found a prevalence of SETs of 0.36%. However, the prevalence of gastric SETs in Korean patients has not been described. Therefore, this study evaluated the prevalence of SETs of the stomach in a Korean patient population. We reviewed endoscopic reports of 11,712 subjects who underwent screening esophagogastroduodenoscopy (EGD) at Hanyang University Hospital between July 2012 and June 2013. Among 11,712 patients, 194 (1.7%) had SET of the stomach. Of these, 71 (prevalence, 0.6%) were male and 123 (prevalence, 1.1%) were female. When grouped by age, the prevalence of SET was as follows: 1.0% for patients in their twenties, 6.2% for those in their thirties, 19.1% for those in their forties, 33.0% for those in their fifties, 30.4% for those in their sixties, and 10.3% for those over 70 years of age. The overall prevalence of gastric SET among healthy examinees was 1.7%. The prevalence of gastric SET increased with age and was higher in female.